The Influence of Leadership, Organizational Commitment, and Job Satisfaction on Employee Performance at the Mozes Kilangin Timika Airport Administration Office in Mimika Regency - Anton Pasoro; Usman Pakasi; Darmanto (Polit Journal Scientific Journal of Politics, 2025)
This study analyzes the influence of leadership, organizational commitment, and job satisfaction on employee performance at the Mozes Kilangin Timika Airport Administration Office. The method used is a quantitative approach strengthened by qualitative triangulation, data were collected through questionnaires distributed to 84 employees and interviews with key informants. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and descriptive analysis. The findings indicate that all three variables, both individually and collectively, exert a positive and significant influence on employee performance. These results highlight the importance of effective leadership, a high level of commitment grounded in a sense of ownership, and job satisfaction fostered by a conducive work environment. Nonetheless, areas for improvement were identified, including policy consistency, transparency in human resource development, and employee benefits. This research underscores the need for integrated management of these factors to achieve optimal and sustainable performance in public service delivery.